Synthesis of ternary copper antimony sulfide via solventless thermolysis or aerosol assisted chemical vapour deposition using metal dithiocarbamates - Fadiyah Makin; Firoz Alam; Mark A. Buckingham; David J. Lewis (Scientific Reports, 2022)
Abstract Copper antimony sulfide (Cu-Sb-S) has recently been proposed as an attractive alternative photovoltaic material due to the earth-abundant and non-toxic nature of the elements, high absorption coefficients and band gaps commensurate with efficient harvesting of solar photonic flux across multiple phases of Cu-Sb-S. These materials are therefore highly desirable and sustainable and scalable deposition techniques to produce them are of interest. In this paper, we demonstrate two facile, low-temperature and inexpensive techniques (solventless thermolysis and aerosol-assisted chemical vapor deposition (AACVD)) for the preparation of binary digenite (Cu1.8S), chalcocite (Cu2S) and stibnite (Sb2S3) and several phases of ternary copper-antimony-sulfide (Cu2xSb2(1−x)Sy, where 0 ≤ x ≤ 1). It was found that by utilising these different techniques and varying the ratio of Cu:Sb, pure phases of ternary chalcostibite (CuSbS2), fematinite (Cu3SbS4) and tetrahedrite (Cu12Sb4S13) can be achieved. Two single-source precursors were investigated for this purpose, namely the diethyldithiocarbamate (DTC) complexes of copper and antimony Cu(DTC)2 and Sb(DTC)3. These were decomposed both individually (to produce binary materials) and combined (to produce ternary materials) at different ratios. From the solventless thermolysis and AACVD methods, either particulate or thin film material was formed, respectively. These materials were then characterised by powder XRD, SEM, EDX and Raman spectroscopies to determine the crystalline phase, material morphology and uniformity of elemental composition. This analysis demonstrated that as the Cu-content increases, the phase of the ternary material changes from chalcostibite (CuSbS2) and fematinite (Cu3SbS4) at a low Cu:Sb ratio to tetrahedrite (Cu12Sb4S13) at a high Cu:Sb ratio.